Reversible Diels–Alder Reaction To Control Wrinkle Patterns: From Dynamic Chemistry to Dynamic Patterns. Issue 41 (30th August 2016) - Hou, Honghao; Yin, Jie; Jiang, Xuesong
Abstract : A facile and robust strategy to produce a reversible wrinkle pattern is presented by controlling a dynamic D–A reaction between furan and maleimide. The smart surface with highly reversible morphology and tunable adhesion, wettability, self‐healing, and transparency is realized by the thermoreversible generation and erasure of the wrinkle pattern, which might find broad applications in functional intelligent materials with properties that can be tuned on‐demand without altering the material's intrinsic properties.